Genetic polymorphism and effect on milk production of CSN2 gene in conventional and local cattle breeds in Croatia - Ivanković, Ante, agronom (Array, 2020)
Over the past three decades, the scientific and public interest has been initiated by studies in which  the negative effect of milk consumption of beta-casein A1 variant has been observed on consumers" health. The production of "A2 milk" is one of the ways to economically increase the competitiveness of small and medium-sized dairy farms. Breeders of endangered local breeds are also interested in reaffirmation through production of "A2 milk". The aim of this study is to determine frequencies of A1 and A2 variants of beta-casein in three commercial and three local breeds of cattle in Croatia, and their relationship with production indicators of commercial breeds in the first three lactations. The genomic DNA was extracted from hair and determination of CSN2 genotypes was conducted by PCR RFLP method. Data for milk yield and chemical composition were provided by the central database. The dominant presence of A2 variant beta-casein in the investigated cattle breeds (0.650-0.758) and the increase in the frequency of A2 beta-casein in the population of Simmental and Istrian cattle were determined.